Group Discussions and Their Organization Technique - Baydullayeva Firuza Akilbekovna (Researchparks Publishing, 2022)
the article deals with the issues based on organizing group discussions and features of techniques in their usage. As it’s known that communicative competence plays an important role in professional activity; they are one of the factors of effective communication. As well as, the success of the development of the educational sphere today largely depends on how much a modern teacher is developed not only as a professional, but also as a person who is able to independently find solutions in various life and professional situations, take responsibility for his choice, possess variable thinking and value consciousness.